Scenarios of Good Anthropocenes in southern Africa. (April 2020) - Hamann, M.; Biggs, R.; Pereira, L.; Preiser, R.; Hichert, T.; Blanchard, R.; Warrington-Coetzee, H.; King, N.; Merrie, A.; Nilsson, W.; Odendaal, P.; Poskitt, S.; et al.
Highlights: Radical, positive scenarios of the future were created on the basis of already existing local-scale initiatives and innovations. These futures were characterized by decentralized governance, localized production systems, connectedness, and empathy. Business-as-usual socio-economic trajectories were abandoned across all futures, but the role of technology in everyday life varied. The creative, participatory process inspired and encouraged an exploration of futures that included significant paradigm shifts. Abstract: In the rapidly changing and uncertain world of the Anthropocene, positive visions of the future could play a crucial role in catalysing deep social-ecological transformations to help guide humanity towards more sustainable and equitable futures. This paper presents the outcomes from a novel visioning process designed to elicit creative and inspirational future scenarios for southern Africa. The approach based scenario development on "seeds of good Anthropocenes", i.e. existing initiatives or technologies that represent current, local-scale innovations for sustainability. A selection of seeds was used to create four distinct, positive visions in a participatory workshop process. Common themes that independently emerged in all four visions were i) decentralized governance and decision-making; ii) a strong emphasis on equity and empathy; iii) high levels of connectedness between people; and iv) a reinforced, respectful relationship with nature. The visions mainly differ in the extent of fusion between people and technology in everyday life, and how much nature plays a role in defining the human experience. The narratives presented here describe worlds that have undergone a more significant paradigm shift towards shared human values and stewardship of resources than is explored in most other ambient narratives for the region. These "Good Anthropocene" scenarios therefore demonstrate more radical, previously unimagined ways of thinking about sustainability futures on the African continent and beyond.